2010
DOI: 10.1021/ef100068m
|View full text |Cite
|
Sign up to set email alerts
|

Gasification and Chemical-Looping Combustion of a Lignite Char in a Fluidized Bed of Iron Oxide

Abstract: Gasification and chemical-looping combustion experiments with a lignite (Hambach) char are reported, using an electrically heated fluidized bed in a 25 mm diameter tube at about 1073 K. The fluidizing gas was CO2 in nitrogen, with either batch or continuous feed of char into a bed of sand or particles of Fe2O3. The experiments were also modeled using the two-phase theory of fluidization; a well-mixed particulate phase is assumed, and the bubble flow is augmented by gasification products. This was combined with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 32 publications
2
80
0
Order By: Relevance
“…The product stream was analyzed during 120 min and no significant amounts of carbonaceous products (CO, CO 2 ) were detected. Therefore it was concluded that the solid-solid contribution to the carbon conversion was negligible in this case, similarly to what was found before by other authors [21,38,52]. Char gasification must proceed as an intermediate step in the coal conversion process using bauxite waste as oxygen carrier.…”
Section: Effect Of the Gasifying Agentsupporting
confidence: 86%
See 1 more Smart Citation
“…The product stream was analyzed during 120 min and no significant amounts of carbonaceous products (CO, CO 2 ) were detected. Therefore it was concluded that the solid-solid contribution to the carbon conversion was negligible in this case, similarly to what was found before by other authors [21,38,52]. Char gasification must proceed as an intermediate step in the coal conversion process using bauxite waste as oxygen carrier.…”
Section: Effect Of the Gasifying Agentsupporting
confidence: 86%
“…The H 2 and CO removal from the gasification products reduced the inhibition effect that both gases, especially H 2 , could have on the gasification process [51]. Similar conclusions were reached before in previous studies using Fe-based oxygen carriers [21,38,52]. The decrease in the inhibition of char gasification can be observed in Figure 5 (B), where the char conversion evolution with time is represented for both sand and bauxite waste experiments.…”
Section: Char Gasification In the Presence Of Bauxite Wastesupporting
confidence: 85%
“…Dennis et al [118,119] have proposed the use of a cycling fed-batch operation for solid fuels in order to reduce the attrition problems associated with the conveying of large quantities of solids in the interconnected fluidized beds configuration. In this operation mode, three consecutive periods of time (fuel feeding, char combustion without fuel feed, and oxygen-carrier regeneration with air) are carried out in only one fluidized reactor.…”
Section: Process Fundamentalsmentioning
confidence: 99%
“…CO 2 can be re-circulated from the flue gases. The use of CO 2 has been proposed for highly reactive solid fuels, such as low-rank coals or biomass [119]. Otherwise, special considerations should be given when using CO 2 as gasification agent depending on the design configuration because of the slow gasification rate with CO 2 , as will be discussed later.…”
Section: In-situ Gasification Chemical-looping Combustion (Ig-clc)mentioning
confidence: 99%
See 1 more Smart Citation